Inside-out and standard vein grafts associated with platelet-rich plasma (PRP) in sciatic nerve repair. A histomorphometric study - Roque,José Sidney (2017)
Abstract Purpose: To evaluated the tubulization technique with standard and inside-out vein, filled or not with platelet-rich plasma (PRP), in sciatic nerve repair. Methods: Seventy male Wistar rats were randomly divided into five groups: IOVNF (Inside-Out Vein with No Filling); IOVPRP (Inside-Out Vein filled with PRP); SVNF (Standard Vein with No Filling); SVPRP (Standard Vein filled with PRP); Sham (Control). The left external jugular vein was used as graft in a 10 mm nervous gap. Results: In the morphological analysis of all groups, myelinated nerve fibers with evident myelin sheath, neoformation of the epineurium and perineurium, organization of intraneural fascicles and blood vessels were observed. In the morphometry of the distal stump fibers, SVPRP group had the highest means regarding fiber diameter (3.63±0.42 μm), axon diameter (2.37±0.31 μm) and myelin sheath area (11.70±0.84 μm2). IOVPRP group had the highest means regarding axon area (4.39±1.16 μm2) and myelin sheath thickness (0.80±0.19 μm). As for values of the fiber area, IOVNF group shows highest means (15.54±0.67 μm2), but are still lower than the values of the Sham group. Conclusion: The graft filled with platelet-rich plasma, with use standard (SVPRP) or inside-out vein (IOVPRP), promoted the improvement in axonal regeneration on sciatic nerve injury.